Long-term methylphenidate exposure and 24-hours blood pressure and left ventricular mass in adolescents and young adults with attention deficit hyperactivity disorder. - Buitelaar, J. K.; van de Loo-Neus, G. H.H.; Hennissen, L.; Greven, C. U.; Hoekstra, P. J.; Nagy, P.; Ramos-Quiroga, A.; Rosenthal, E.; Kabir, S.; Man, K. K.C.; IC, Wong; Coghill, D.; et al. (European Neuropsychopharmacology, 2022)
Young people with attention deficit hyperactivity disorder (ADHD) are now being treated with psychostimulant medication for longer than was previously the case and are increasingly likely to remain on methylphenidate into adolescence and adulthood. This study was designed to determine whether the long-term use of methylphenidate (MPH, immediate release or extended release) increases blood pressure and left ventricular mass (LVM) identified by echocardiography in adolescents and young adults with ADHD aged 12-25 years. In a five-site cross-sectional design two groups were compared for 24- hour blood pressure and heart rate (HR) registrations and LVM: 1) adolescents and young adults with ADHD who had been treated with MPH for > 2 years (N=162, age mean (SD) 15.6 (3.0)), and 2) adolescents and young adults with ADHD who had never been treated with methylphenidate (N=71, age mean 17.4 (4.2)). The analyses were controlled for propensity scores derived from age, sex, height, weight, and 19 relevant background variables. A blood pressure indicative of hypertension (>95th percentile) was observed in 12.2% (95% confidence interval 7.3 - 18.9%) of the participants in the MPH treated group and in 9.6% (95%CI 3.2 - 21.0%) of the MPH naïve group, with overlapping intervals. The 24-hour recorded systolic blood pressure (SBP) and HR were significantly higher during daytime in medicated individuals with ADHD than in those with unmedicated ADHD, but were similar in both groups during the night. 24-hour diastolic blood pressure (DBP) did not differ between both groups during either daytime or at night. LVM, corrected for body-surface area (LVMBSA), also did not differ between the two groups (p=0.20, controlling for confounders). Further, MPH daily dose and duration of treatment were unrelated to LVMBSA, SBP, and DBP. Long-term MPH use in adolescents and young adults with ADHD is associated with small but significant increases of SBP and HR during daytime. Given the current sample size, the proportions of hypertension do not differ significantly between MPH treated and MPH-naïve individuals with ADHD. Future studies with larger samples, longer treatment duration, and/or with within-subject designs are necessary. The results do, however, further support recommendations that highlight the importance of monitoring blood pressure and HR during MPH treatment.
EVALuna2:508778